(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Schleichera oleosa (Lour.) Oken. is a medicinal plant of Bangladesh with enormous traditional applications in folk medicine. The current study was designed to isolate the secondary metabolites by successive chromatographic separation of n-hexane and dichloromethane soluble fractions of a methanol extract of leaves of S. oleosa. A total of four compounds were separated and identified as 5,7-dihydroxy-4’-methoxyflavone, stigmasterol, lupeol and betulinic acid. The structures of the isolated compounds were elucidated by analysis of their 1H NMR data and comparison with published values. Bangladesh Pharmaceutical Journal 24(1): 33-36, 2021